2000
DOI: 10.2355/isijinternational.40.613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silicon on the Kinetics of Nb(C, N) Precipitation during the Hot Working of Nb-bearing Steels.

Abstract: The effect of Si on the rate of Nb(C, N) precipitation was investigated by using fractional softening measurements. Compression specimens, with diameters of 7.6 mm and lengths of 11.4 mm, were prepared from four Nb microalloyed steels containing a range of Si concentrations from 0.01 mass% to 0.41 mass%. Double-hit compression tests, with a strain of 0.3 for each pass and a strain rate of 0.1/sec., were employed. A solution heat treatment was applied immediately prior to each test. It was found that the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…It has been suggested that Si addition decreases the solubility of V(C, N) because it increases the activities of C and N. It therefore, increases the precipitation rate of V(C, N), in microalloyed steels and can prevent softening during hot rolling. 1) Dong et al 2) came to somewhat similar conclusions in their investigation of Nb steels. They found that the addition of Si increases the rate of Nb(C, N) precipitation in hot deformed austenite.…”
Section: Introductionsupporting
confidence: 62%
“…It has been suggested that Si addition decreases the solubility of V(C, N) because it increases the activities of C and N. It therefore, increases the precipitation rate of V(C, N), in microalloyed steels and can prevent softening during hot rolling. 1) Dong et al 2) came to somewhat similar conclusions in their investigation of Nb steels. They found that the addition of Si increases the rate of Nb(C, N) precipitation in hot deformed austenite.…”
Section: Introductionsupporting
confidence: 62%
“…However, when rolling temperature raise to 940 • C, the stress values of latter three passes are on the same level, the characteristic of the third pass is similar with the feature of DRX. The same results can be presented in the diagrams of mean flow stress (MFS), decreasing of MFS represents the occurrence of DRX [17], as shown in Fig. 14.…”
Section: Dynamic Recrystallization Behaviors In Strip Rollingsupporting
confidence: 63%
“…(2) and (5), respectively. A total of 72 data points, collated from the literature [6][7][8][9]21,22,[27][28][29][30][31] were plotted in this way in Fig. 6.…”
Section: Interpretation Of the Mapmentioning
confidence: 99%